Gain of FGF4 is a frequent event in KIT/PDGFRA/SDH/RAS‐P WT GIST. Issue 9 (16th April 2019) - Urbini, Milena; Indio, Valentina; Tarantino, Giuseppe; Ravegnini, Gloria; Angelini, Sabrina; Nannini, Margherita; Saponara, Maristella; Santini, Donatella; Ceccarelli, Claudio; Fiorentino, Michelangelo; Vincenzi, Bruno; Fumagalli, Elena; et al.
Abstract: Gastrointestinal stromal tumors (GIST) lacking mutations in KIT/PDGFRA or RAS pathways and retaining an intact SDH complex are usually referred to as KIT/PDGFRA/SDH/RAS‐P WT GIST or more simply quadruple WT GIST ( 5% of all GIST). Despite efforts made, no recurrent genetic event in quadruple WT GIST has been identified so far. To further investigate this disease, we performed high throughput copy number analysis on quadruple WT GIST specimens identifying a recurrent focal gain in band 11q13.3 (involving FGF3/FGF4 ) in 6/8 cases. This event was not found in the other molecular GIST subgroups. FGF3/FGF4 duplication was associated with high expression of FGF4, both at mRNA and protein level, a growth factor normally not expressed in adult tissues or in KIT/PDGFRA‐mutated GIST. FGFR1 was found to be the predominant FGF receptor expressed and phosphorylation of AKT was detected, suggesting that a FGF4‐FGFR1 autocrine loop could stimulate downstream signaling in quadruple WT GIST. Together with the recent reports of quadruple WT cases carrying FGFR1 activating alterations, these findings strengthen the hypothesis of a potential involvement of FGFR pathway deregulation in quadruple WT GIST, which may represent a rationale for novel therapeutic approaches.